An Online Path Planner for Bandwidth-aware Aerial Camera Networks - Mohammad Rezaei; Gioacchino Manfredi; Vito Racanelli; Luca De Cicco; Saverio Mascolo (2025 17th International Congress on Ultra Modern Telecommunications and Control Systems and Workshops (ICUMT), 2025)
Unmanned Aerial Vehicle (UAV) swarms equipped with cameras are of growing interest for applications such as surveillance and object detection, transmitting real-time videos to a Ground Control Station (GCS) over the Internet. The quality of the videos received depends on both the available network bandwidth and the altitude of the drones. In this paper, a swarm of UAVs is given the task of scanning an area of interest while guaranteeing an overlap between the videos captured by each UAV for post-processing reasons, e.g. video stitching. Drones are enabled to adjust their altitude based on the available bandwidth to enhance visual quality. This work proposes a bandwidth-aware online path planner to maximize the coverage of a given area by extending the classic lawnmower path planner. The UAVs use Nonlinear Model Predictive Control (NMPC) to maximize both the total coverage area and the quality of the videos sent to the GCS. Simulations demonstrate the effectiveness of the proposed approach with different swarm configurations.
Keywords: Visualization; Surveillance; Bandwidth; Autonomous aerial vehicles; Cameras; Real-time systems; Telecommunications; Videos; Drones; Predictive control